Child language an interdisciplinary guide to theory and research - Abrahamsen, Adele A. (University Park Press, 1977)
Over 1500 references to English-language books, Ph. D. dissertations, and journal articles published during 1894-1977. Citations deal primarily with normal, first-language acquisition. Intended for all personnel in child language research. Classified arrangement. Entry gives bibliographical information and annotation. Author, subject indexes.